A Comparative Study of Typhoon Hato (2017) and Typhoon Mangkhut (2018)—Their Impacts on Coastal Inundation in Macau. Issue 12 (27th December 2019) - Yang, Jie; Li, Linlin; Zhao, Kuifeng; Wang, Peitao; Wang, Dong; Sou, In Mei; Yang, Zhengtong; Hu, Jie; Tang, Xiaochun; Mok, Kai Meng; Liu, Philip Li‐Fan
Abstract: Typhoons Hato (2017) and Typhoon Mangkhut (2018) struck the Pearl River Delta, China, in two consecutive years, causing intense flooding and severe damage along the coast, especially in Macau. These two typhoons are extreme events because of their record‐breaking storm tides, and they are typical typhoons in terms of their track forward directions, which affect the coast of Guangdong Province, China. This paper analyzes and compares the physical processes of these two major typhoons. We first report the results of our posttyphoon surveys in Macau and the constructed inundation maps for both typhoon events. The inundation maps in conjunction with measured wind, atmospheric pressure, and wave data are used to validate a package of numerical models that simulate fully coupled tide‐surge‐wave fields during a typhoon. We quantify storm surges and wave heights in the Pearl River Delta. The surge around Macau was mainly affected by wind, while atmosphere pressure and ocean waves played a secondary role. In additional to inundation depth, we also investigate inundation durations and flow velocities. Typhoon Mangkhut made its landfall at much lower tidal level than that of Typhoon Hato. However, Typhoon Mangkhut generated much larger storm surge with larger affected areas and significantly longer inundation durations. We attribute the causes mainly to Typhoon Mangkhut's storm size, which was almost three times larger than that of Typhoon Hato. Plain Language Summary: Typhoons Hato (2017) and Typhoon Mangkhut (2018) are two record‐breaking typhoons, which struck the Pearl River Delta, China, in two consecutive years. We conduct timely posttyphoon surveys and construct high‐resolution inundation maps in Macau where the severest impacts by both typhoons are evident. By conducting a fully coupled numerical simulation for tide‐surge‐wave, we reproduce the physical processes of these two typhoon events in the Pearl River Estuary. Typhoon Mangkhut and Typhoon Hato represent two distinct types of typhoons, which are equally dangerous. Typhoon Mangkhut is enormous in size, causing storm surge hazard in a much larger spatial coverage with much longer flood duration in the Pearl River Estuary. Typhoon Hato, which strengthened unexpectedly from Categories 1 to 3 on the Saffir‐Simpson scale in 5 hr just before its landfall, increased the risk of inadequate evacuation efforts, large causalities, and property damage. Key Points: We compare the physical processes of two record‐breaking typhoons using the field observations and numerical simulations Storm size plays a key role in generating larger storm surges with longer inundation duration for Typhoon Mangkhut The inundation processes in Macau are investigated, including time histories of inundation depth, flooding velocity, and flooding duration